From monomers to polymers: steric and supramolecular effects on dimensionality of coordination architectures of heteroleptic mercury(ii) halogenide–tetradentate Schiff base complexes1. Issue 18 (14th May 2015) - Mahmoudi, Ghodrat; Stilinović, Vladimir; Gargari, Masoumeh Servati; Bauzá, Antonio; Zaragoza, Guillermo; Kaminsky, Werner; Lynch, Vincent; Choquesillo-Lazarte, Duane; Sivakumar, K.; Khandar, Ali Akbar; Frontera, Antonio
<x xml:space="preserve">Abstract</x> We report the synthesis and X-ray characterisation of six mercury(ii) halogenide–tetradentate Schiff base complexes.